Relationship between Body Image, Growth Mindset, Grit, and Successful Aging in Korean Elderly: Moderated Mediation Effect of Hope (Medico Legal Update, 2020)
Background/Objectives: This study examines the moderated mediation effect of hope on the relationship between body image, growth mindset, grit, and successful aging in 422 elderly people in Korea.Method/Statistical Analysis: Descriptive statistics analysis, reliability analysis, correlation analysis, and moderated mediation effect analysis were done using SPSS Win.25.0 and PROCESS macro version 3.4.Findings: First, there was a statistically significant positive correlation between body image, growth mindset, hope, grit, and successful aging. Second, hope moderated the mediating effect of growth mindset and grit in the relationship between body image and successful aging.Improvements/Applications: This result shows that the body image of the elderly in Korean society influences successful aging through growth mindset and grit. It will be a way to increase successful aging.